Accurate Kinetics of Cyclization Reactions of the Large-Size Hydroperoxy Methyl-Ester Radicals Investigated by the Isodesmic Reaction Correction Method - Li, Tao; Chen, Siyu; Li, Juanqin; Zhu, Quan; Li, Zerong (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2023)
The cyclization reactions of hydroperoxymethylester radicals are pivotal in low-temperature methyl-ester combustion but limited experimental and theoretical kinetic data pose challenges. Prior research has drawn upon analogous hydroperoxy alkyl radical cyclization reactions to approximate rate constants and might inaccurately represent ester group-specific behavior. This study systematically investigates these kinetics, accounting for ester group effects and computational complexities in large molecular systems. The reactions are categorized into 11 classes based on cyclic transition state size and -OOH/radical positions. Energy barriers and high-pressure-limit rate constants are calculated using the isodesmic reaction correction method, validated, and applied to 24 subclasses based on carbon sites connected to -OOH and radical moieties. Subclass high-pressure-limit rate rules are derived through averaging rate constants. Analysis reveals uncertainties within acceptable chemical accuracy limits, validating the reaction classification and rate rules. We conduct comparative analyses with values from analogous alkyl reactions in established mechanisms while comparing our results with the high-pressure-limit rate rules for analogous alkane reactions. These comparisons reveal notable disparities, emphasizing the ester group's influence and necessitating tailored ester-specific rate rules. These findings hold promise for improving automatic reaction mechanism generation, particularly for large methyl esters.The cyclization reactions of hydroperoxymethylester radicals are pivotal in low-temperature methyl-ester combustion but limited experimental and theoretical kinetic data pose challenges. Prior research has drawn upon analogous hydroperoxy alkyl radical cyclization reactions to approximate rate constants and might inaccurately represent ester group-specific behavior. This study systematically investigates these kinetics, accounting for ester group effects and computational complexities in large molecular systems. The reactions are categorized into 11 classes based on cyclic transition state size and -OOH/radical positions. Energy barriers and high-pressure-limit rate constants are calculated using the isodesmic reaction correction method, validated, and applied to 24 subclasses based on carbon sites connected to -OOH and radical moieties. Subclass high-pressure-limit rate rules are derived through averaging rate constants. Analysis reveals uncertainties within acceptable chemical accuracy limits, validating the reaction classification and rate rules. We conduct comparative analyses with values from analogous alkyl reactions in established mechanisms while comparing our results with the high-pressure-limit rate rules for analogous alkane reactions. These comparisons reveal notable disparities, emphasizing the ester group's influence and necessitating tailored ester-specific rate rules. These findings hold promise for improving automatic reaction mechanism generation, particularly for large methyl esters.